EFEKTIVITAS MODEL PEMBELAJARAN PROJECT BASED LEARNING DALAM MENINGKATKAN MOTIVASI BELAJAR IPAS SISWA KELAS V SD MUHAMMADIYAH AMBARKETAWANG 2 - Nadiya Fithriani Lubis; Raden Wisnu Wijaya Dewojati (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2025)
This research is motivated by students' relatively low motivation to learn science, resulting in boredom and a general lack of active participation in learning activities. Furthermore, in elementary school science, teachers often fail to implement learning models that capture students' attention and enhance their motivation, particularly regarding the food chain. Therefore, this study aims to determine the effectiveness of the project-based learning model and to identify supporting and inhibiting factors in improving fifth-grade students' motivation to learn science. This study employed a quantitative approach and a pre-experimental one-group pretest-posttest design. Twenty-four fifth-grade students at Muhammadiyah Ambarketawang 2 Elementary School participated in the study. Data collection used a science motivation questionnaire and documentation. Data analysis included normality tests, homogeneity tests, and hypothesis testing using SPSS version 25. The results showed an average pretest score of 53.42 for science motivation, followed by a posttest score of 63.83. Based on the results of hypothesis testing using paired sample t-test with the help of SPSS version 25, the significance value (Sig. 2-tailed) was 0.000 <0.05, so Ha was accepted and H0 was rejected, which means there was a significant difference. Thus, it can be concluded that the use of the project-based learning model is effective in increasing the motivation to learn science in grade V students of SD Muhammadiyah Ambarketawang 2, especially in the food chain material.